Boundedness for Commutators of Bilinear θ-Type Calderón-Zygmund Operators on Nonhomogeneous Metric Measure Spaces. (9th January 2017) - Xie, Rulong; Shu, Lisheng; Sun, Aiwen
Abstract : Let ( X, d, μ ) be a nonhomogeneous metric measure space. In this paper, the boundedness for commutators generated by bilinear θ -type Calderón-Zygmund operators and R B M O ( μ ) functions on ( X, d, μ ) is obtained.